Dimethylthetin can substitute for glycine betaine as an osmoprotectant molecule for Escherichia coli. - Chambers, S T (1987)
Glycine betaine is believed to be the most active naturally occurring osmoprotectant molecule for Escherichia coli and other bacteria. It is a dipolar ion possessing a quaternary ammonimum group and a carboxylic acid group. To examine the molecular requirements for osmoprotective activity, dimethylthetin was compared with glycine betaine. Dimethylthetin is identical to glycine betaine except for substitution of dimethyl sulfonium for the quaternary nitrogen group. Dimethylthetin was found to be about equally as effective as glycine betaine in permitting E. coli to grow in hypertonic NaCl, and both compounds were recovered almost completely from bacterial cells grown in the presence of hypertonic NaCl. 3-Dimethylsulfonioproprionate, an analog of dimethylthetin observed in marine algae, and 3-Dimethylsulfonio-2-methylproprionate were found to be less active. Dimethylthetin may prove useful as a molecular probe to study betaine metabolism and as a model for the development of antibacterial agents.